2020
DOI: 10.1001/jamanetworkopen.2020.22933
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Risk of Progression of Low-Risk Branch-Duct Intraductal Papillary Mucinous Neoplasms

Abstract: IMPORTANCE Branch-duct intraductal papillary mucinous neoplasms (BD-IPMNs) are common pancreatic preneoplastic lesions, but their surveillance is not personalized. OBJECTIVE To investigate patient-and cyst-related factors associated with progression into worrisome features (WFs) or high-risk stigmata (HRS) categories of BD-IPMNs. DESIGN, SETTING, AND PARTICIPANTS Cyst-and patient-related factors of consecutive BD-IPMNs without WFs or HRS in 540 patients diagnosed from 2009 to 2018 with at least 12 months' surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…The cohorts from the two Italian centers have been described previously. 25 The cyst surveillance databases received…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cohorts from the two Italian centers have been described previously. 25 The cyst surveillance databases received…”
Section: Methodsmentioning
confidence: 99%
“…We combined prospectively maintained databases on pancreatic cyst surveillance from three university hospitals: the Yale New Haven Hospital (New Haven, USA), the San Raffaele Scientific Institute (Milan, Italy), and the San Andrea Hospital (Rome, Italy). The cohorts from the two Italian centers have been described previously 25 . The cyst surveillance databases received institutional review board approval in all centers (2000020031 Yale, 133/2016 San Raffaele, 251/2012 San Andrea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capurso et al [ 46 ] investigated patient- and cyst-related factors associated with progression into WF or HRS categories of BD-IPMNs. This study included 540 patients diagnosed from 2009 to 2018 with at least 12 mo of surveillance until February 28, 2020.…”
Section: Management Of Ipmnsmentioning
confidence: 99%
“…The higher association of AA group compared to 00 group with progression was also associated. The authors concluded that IPMN diameter alone is not a sufficient for the assessment of progression risk; however, it is useful in correlation with correlated with other features in observation of BD-IPMN patients[ 46 ].…”
Section: Management Of Ipmnsmentioning
confidence: 99%